PENGARUH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE DAN KEPEMILIKAN ASING TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR KESEHATAN - Vanesa Dwi Octavia; Mariana Mariana (Jurnal Akuntansi Kompetif, 2026)
This study aims to obtain empirical evidence on the effect of Environmental, Social, and Governance (ESG) disclosure and foreign ownership on corporate profitability. Employing multiple linear regression, this study investigates the relationship between ESG disclosure, foreign ownership, and profitability among healthcare sector companies listed on the Indonesia Stock Exchange (IDX) over the 2022–2024 period. The findings reveal that both ESG disclosure and foreign ownership exert a positive influence on corporate profitability. This indicates that greater transparency in ESG practices, along with the participation of foreign investors, contributes to improved financial performance. Overall, these results are expected to provide insights for companies in enhancing profitability through strengthening ESG disclosure and optimizing the role of foreign ownership.